Biogeochemical profiling and taxonomic characterization of municipal landfill site by metagenomic sequencing. (May 2022) - Gupta, Juhi; Rathour, Rashmi; Dupont, Christopher; Mishra, Arti; Shekhar Thakur, Indu
Graphical abstract: Highlights: The Metagenomic soil sample was assessed for its microbial diversity. The taxonomic analysis revealed Proteobacteria to be the dominant taxon. Results showed significant reads for aromatic compound degradation and stress tolerance. Biogeochemical profiling for multiple metabolism pathways was done. Abstract: Most of the discarded waste material paves their way to the utmost common dumping grounds, Landfills. Despite their widespread use, the landfill microbiomes are still not well characterized. Metagenomics approach provides insight into the identification of operational parameters influencing the microbiome composition and their biodegradation competencies. The metagenomic DNA was prepared to explore taxonomical community structure, phylogenetic relationships, and functional profile at the same time. A total of 100, 021, 052 high-quality filtered reads were acquired with a GC abundance of 62.59%. Taxonomical abundance revealed the dominance of phylum Proteobacteria and genes involved in biomolecules metabolism, aromatic compound degradation, stress tolerance, xenobiotic biodegradation etc. were revealed functionally. The intricate heterogeneous environment of landfill revealed well flourished biogeochemical metabolic profiles including nitrogen metabolism. This is the first study for the generated metagenome of Ghazipur landfill and the obtained results propose that microbial communities in landfill settings are far more intricate than expected. It remain mostly unexplored which demands the usage of multiple platforms for a better understanding.